Response of atmospheric composition to COVID-19 lockdown measures during spring in the Paris region (France) - J.-E. Petit (Copernicus Publications, 2021)
Since early 2020, the COVID-19 pandemic has led to lockdowns at national scales. These lockdowns resulted in large cuts of atmospheric pollutant emissions, notably related to the vehicular traffic source, especially during spring 2020. As a result, air quality changed in manners that are still currently under investigation. The robust quantitative assessment of the impact of lockdown measures on ambient concentrations is however hindered by weather variability. In order to circumvent this difficulty, an innovative methodology has been developed. The Analog Application for Air Quality (A3Q) method is based on the comparison of each day of lockdown to a group of analog days having similar meteorological conditions. The A3Q method has been successfully evaluated and applied to a comprehensive in situ dataset of primary and secondary pollutants obtained at the SIRTA observatory, a suburban background site of the megacity of Paris (France). The overall slight decrease of submicron particulate matter (PM1) concentrations (−14 %) compared to business-as-usual conditions conceals contrasting behaviors. Primary traffic tracers (NOx and traffic-related carbonaceous aerosols) dropped by 42 %–66 % during the lockdown period. Further, the A3Q method enabled us to characterize changes triggered by NOx decreases. Particulate nitrate and secondary organic aerosols (SOAs), two of the main springtime aerosol components in northwestern Europe, decreased by −45 % and −25 %, respectively. A NOx relationship emphasizes the interest of NOx mitigation policies at the regional (i.e., city) scale, although long-range pollution advection sporadically overcompensated for regional decreases. Variations of the oxidation state of SOA suggest discrepancies in SOA formation processes. At the same time, the expected ozone increase (+20 %) underlines the negative feedback of NO titration. These results provide a quasi-comprehensive observation-based insight for mitigation policies regarding air quality in future low-carbon urban areas.